A thermodynamic criterion for the choice of flux and its validity in NaBO2-fluxed β-BaB2O4 crystal growth. Issue 15 (29th March 2022) - Luo, Wen; Wan, Songming; Jiang, Shengjie; Li, Bin
Abstract : This work provides a promising theoretical methodology to solve the most fundamental problem in flux crystal growth. Abstract : The choice of flux is critical and also challenging to flux crystal growth. In order to address this issue, a thermodynamic criterion for the choice of flux is proposed. Density functional theory (DFT) computations were used to study the atomic chemical potentials of β-BaB2 O4 and NaBO2 in the BaB2 O4 –NaBO2 eutectic system. The results verify the validity of the criterion.